2020
DOI: 10.1186/s13550-020-00726-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in [18F]FDG uptake in BAT of UCP1 −/− and UCP1 +/+ during adrenergic stimulation of non-shivering thermogenesis

Abstract: Background Brown adipose tissue (BAT) is a fat tissue found in most mammals that helps regulate energy balance and core body temperature through a sympathetic process known as non-shivering thermogenesis. BAT activity is commonly detected and quantified in [18F]FDG positron emission tomography/computed tomography (PET/CT) scans, and radiotracer uptake in BAT during adrenergic stimulation is often used as a surrogate measure for identifying thermogenic activity in the tissue. BAT thermogenesis is believed to be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As a result, a wide range of conclusions about BAT distribution is inevitable when quantifying this tissue with 18 F-FDG standardized uptake values [11,12]. Additionally, although 18 F-FDG-PET has suggested that BAT activity is significantly lower in patients with obesity compared with lean patients [13], the dissociation between BAT activity and glucose uptake has demonstrated that these results may not be reliable [9,10,14]. Computed tomography (CT) and magnetic resonance imaging have also been explored as a method of locating and quantifying BAT [15,16], but their results depend on BAT hydration [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a wide range of conclusions about BAT distribution is inevitable when quantifying this tissue with 18 F-FDG standardized uptake values [11,12]. Additionally, although 18 F-FDG-PET has suggested that BAT activity is significantly lower in patients with obesity compared with lean patients [13], the dissociation between BAT activity and glucose uptake has demonstrated that these results may not be reliable [9,10,14]. Computed tomography (CT) and magnetic resonance imaging have also been explored as a method of locating and quantifying BAT [15,16], but their results depend on BAT hydration [17].…”
Section: Introductionmentioning
confidence: 99%
“…The use of NHPs in this study is motivated by their phylogenetic similarity with humans in terms of adipose distributions and progression of obesity and metabolic diseases [29]. In contrast to mice, which tend to have BAT predominantly concentrated in the interscapular region [14,19,26], humans and NHPs have very similar anatomical distributions of BAT, with the main depots located in the supraclavicular and axillary regions [30,31]. Rhesus and vervet monkeys, in particular, spontaneously develop obesity and diabetes as they age at prevalence rates comparable to that of humans [31].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the reduced volume of inguinal fat and the observed heterogeneity of the browning process in this tissue, coupled with the limited resolution of PET will make any quantification extremely challenging. MR thermometry and infrared thermometry have been used by us 34,40,41 and others 42,43 to assess thermogenic activity of the main BAT depot in vivo. However, decoupling the increase in thermogenic activity of the inguinal depot from the much larger increase www.nature.com/scientificreports/ in thermogenic activity of BAT will be impossible, especially considering that in anesthetized mice thermogenic activity in BAT alone can increase whole body temperature by several degrees Celsius 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Mice are known to have brown adipose tissue (BAT) in the neck region which is prone to accumulate [ 18 F]FDG. Proximity of brown fat as well as myocardial tissue to arterial segments poses a challenge in vascular imaging 26 , 27 . Accumulation in brown fat was minimized by assuring that the mice were kept warm at all times following tracer injection and during scans.…”
Section: Discussionmentioning
confidence: 99%